Innovation development of the construction complex in the region on the basis of cluster approach - Yuliya Georgievna Lavrikova; Svetlana Nikolaevna Kotlyarova (Economic and Social Changes: Facts, Trends, Forecast, 2014)
The article substantiates the necessity of using cluster approach in the development of the region’s construction complex for increasing its innovation activity. The formation and development of the regional construction clusters can facilitate the formation of innovation system in the construction complex and integration of different types of innovation. Clusters are also an effective mechanism under the conditions of the market economy; they can unite independent organizations for achieving common strategic goals. Taking the construction cluster of the Ural as an example, the authors discuss the opportunities of using its potential for different purposes, including for the investment development of the Arctic territories. The article shows that cluster can provide innovation-inactive Northern territories with complex innovation construction solutions